Effect of chronic endurance exercise on retention of dietary protein - Friedman, J. E.; Lemon, P. W. (International Journal of Sports Medicine, 1989)
On two separate occasions, five well-trained endurance runners (VO2max = 71 +/- 5 ml/kg/min; means +/- SD) consumed a meat-free diet for 6 days. For one trial the subjects consumed the recommended dietary allowance (RDA) of protein (REC-PRO = 0.86 +/- 0.23 g/kg body wt/day). Protein intake for the other trial was 1.7 times higher (HI-PRO = 1.49 +/- 0.29 g/kg body wt/day). Each subject followed his regular training program (12-16 km running/day), and on day 5 of each diet completed a treadmill run at a similar intensity and duration (75 min at 72% VO2max). Seventy-two hour urinary urea N loss (days 4, 5, and 6 of each diet) and day 5 exercise sweat urea N excretion were measured. Serum urea N and creatinine increased significantly during the treadmill run under both dietary conditions (P less than 0.05). No significances between diet differences were observed in sweat or urinary urea N excretion; however, excretion of both tended to be higher on the REC-PRO diet than on the HI-PRO diet. The differences in protein intake combined with the nitrogen excretion measures resulted in significant differences in estimated whole-body nitrogen retention between the two treatments. Nitrogen retention (means +/- SE) remained positive during the HI-PRO trial (2.41 +/- 1.99 g/day) but was significantly (P less than 0.005) reduced to -5.29 +/- 2.58 g/day during the REC-PRO trial. These results suggest that the current protein RDA may be inadequate for athletes engaging in chronic high-intensity endurance exercise. Future studies are needed to confirm this observation.